Peptide and protein folding - Chasse, Gregory Adam (2001)
Ab initio peptide folding, and its role in the reductionistic approach towards the understanding of protein folding are discussed from the points of view of past, present and possible future developments. It is believed that after the initial holistic approach, we are now at a new epoch, which will be dominated by reductionism. New quantitative mathematical models will be the result of the reductionistic approach that will lead toward a new, more sophisticated holistic era.